Illustration of bounded ambiguity. II, The case of the pharmaceutical firm - Alvesson, Mats, 1956- ([London] : SAGE, 2016)
This case study illustrates the concept of ambiguity in an organization and how it can be bounded. A pharmaceutical firm, Pharma, had a distinct lack of success in its research and development of new products. From interviews with staff, it was clear that there were a number of perceived reasons as to why the new products weren't successful. However, it was clear that many shared the view that more and better management would be the best solution.
Originally Published in: Alvesson, M. (2012). Illustration of Bounded Ambiguity II: The Case of the Pharmaceutical Firm. In Understanding organizational culture (2nd ed., pp. 149-150). London: SAGE Publications Ltd. ISBN: 9780857025586.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Corporate culture -- Case studies; New products -- Case studies; Success in business -- Case studies